The Application of Gold Thread Embroidery on Pashmina with Acehnese Motifs - Nurbaiti, Nurbaiti; Dewi, Rosmala; Widia, Irda (Riwayat: Educational Journal of History and Humanities, 2025)
Gold thread embroidery, or kasab, is a traditional craft in Aceh, Indonesia. It refers to the art of hand embroidery using gold threads to adorn fabric with various intricate motifs. Pashmina is a type of long scarf worn primarily by women at formal events. This study aims to design an Acehnese motif on pashmina through the application of gold thread embroidery, apply the Acehnese motifs on pashmina using gold thread embroidery, and assess consumer acceptance of pashmina products with Acehnese motifs and gold thread embroidery applications. The data collection methods used in this research include applied experiments, documentation, literature reviews, and surveys. The data obtained from the experiments were analysed descriptively, while the survey data were processed using quantitative methods. The results of the study indicate that pashmina model 1 features the Bungong Campli (chili flower) motif on a maroon-coloured pashmina, while model 2 features the Bungong Sagoe (corner flower) motif on a black pashmina. Survey responses revealed that most respondents favored the motif design of Pashmina model 1, which conveyed a sense of authenticity. Regarding embroidery technique, model 1 was considered neater and more elegant. Respondents also noted that the placement of sequins on the black pashmina (model 2) added a luxurious effect, contributing to the creation of a new fashion trend. Furthermore, respondents felt that the placement of tassels on model 2 complemented the motif and overall design. In terms of color coordination, the gold thread on both the maroon and black pashmina fabrics was considered to enhance the aesthetic appeal, adding an elegant, luxurious, and distinct Acehnese touch. Lastly, respondents agreed that model 1 would be highly suitable for formal occasions, with the gold thread embroidery giving it an elegant and luxurious appearance, positioning it as an innovative development in the fashion industry.